Indonesian Maritime Diplomacy: Building Strategic Alliances for Sovereignty at Sea - Saputra, Rizki Marman; Rusliwa Somantri, Gumilar; Subroto, Athor; Marsetio, Marsetio (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This research aims to analyze Indonesia's maritime diplomacy strategy to build strategic alliances to maintain Indonesia's maritime sovereignty. The research method used is a literary study presented descriptively intending to study individuals, groups, organizations, or complex events bound by a certain context. The data collection technique used analyzes documents relevant to the research theme, both from newspapers, national journals, and books with an analytical focus as explained in the theory of Liberal Institutionalism, namely international cooperation and global institutions. Meanwhile, the data analysis techniques used in this research are data reduction, data presentation, and conclusion. The research results show that through effective maritime diplomacy and strategic alliances, Indonesia has succeeded in strengthening its geopolitical position in the Asia-Pacific region, increasing the security of maritime trade routes, and maximizing maritime economic potential. These results show that the Liberal Institutionalism approach can significantly contribute to maintaining Indonesia's maritime sovereignty and security. It is important to pay attention to security, economic and environmental aspects. To maintain this sovereignty, international cooperation is needed through strategic alliances with various countries. This study shows how Indonesia has succeeded in building this alliance.